2019
DOI: 10.3389/fimmu.2019.02655
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Gut Microbiota and Acute Restraint Stress in Peripheral Structures of the Hypothalamic–Pituitary–Adrenal Axis and the Intestine of Male Mice

Abstract: The gut microbiota play an important role in shaping brain functions and behavior, including the activity of the hypothalamus-pituitary-adrenocortical (HPA) axis. However, little is known about the effect of the microbiota on the distinct structures (hypothalamus, pituitary, and adrenals) of the HPA axis. In the present study, we analyzed the influence of the microbiota on acute restraint stress (ARS) response in the pituitary, adrenal gland, and intestine, an organ of extra-adrenal glucocorticoid synthesis. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 52 publications
2
35
0
Order By: Relevance
“…Recently, an expert insight indicated that intestinal microbiota-bile acid-brain axis may participate in the development and progression of AD [68]. Also, the intestinal microbiota plays a role in the regulation of the hypothalamic-pituitary-adrenal axis and is critical for the stress response [69]. Finally, evidences have proved that intestinal microbiota can modulate neuroinflammatory response, and the fact that diseases or the complications with cognitive dysfunction such as AD, PD, depression, as well as postoperative dysfunction in the present study are closely correlated with neuroinflammatory response [65,70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an expert insight indicated that intestinal microbiota-bile acid-brain axis may participate in the development and progression of AD [68]. Also, the intestinal microbiota plays a role in the regulation of the hypothalamic-pituitary-adrenal axis and is critical for the stress response [69]. Finally, evidences have proved that intestinal microbiota can modulate neuroinflammatory response, and the fact that diseases or the complications with cognitive dysfunction such as AD, PD, depression, as well as postoperative dysfunction in the present study are closely correlated with neuroinflammatory response [65,70,71].…”
Section: Discussionmentioning
confidence: 99%
“…(2) hypothalamus-pituitary-adrenal (HPA) axis plays a core role in communication of gut microbiota and the brain; and (3) gut-brain-microbiota axis provides a new treatment target for depression, autism, and Parkinson disease [150][151][152][153][154][155]. A recent study revealed that mycobiota regulates expression of genes in the kynurenine pathway and associated micro-RNAs (miRNAs) in the hippocampus in a sex-depend manner [156], suggesting a possible gut mycobiota-brain axis [5].…”
Section: Gut-brain Axis and Gut Mycobiotamentioning
confidence: 99%
“…Essential HTN is strongly correlated with pressure, and strong mental stress is consistently involved in the development of these conditions. 3 , 39 Therefore, we used the restraint stress rat model, that accelerates cardiovascular damage and HTN on account of bondage stress in our study. While mechanisms that regulate intestinal permeability have been widely studied, little is known on how the colon protects itself from restraint stress.…”
Section: Discussionmentioning
confidence: 99%
“…The main microbiota remains similar among most individuals but there is also slight difference from person to person. Several factors, such as genetics, 60 dietary patterns, 61 , 62 mental stress 39 and geographical region 63 could account for the reason, making them both highly dynamic and susceptible to transient changes. 57 , 62 Previous research has investigated the role of gut microbiota in autoimmune, multiple infectious and metabolic diseases, such as IBD, Clostridium difficile infection and diabetes.…”
Section: Discussionmentioning
confidence: 99%